The Impact of e-Service Quality on Customer e-Satisfaction, e-Loyalty, and Brand Equity: A Study on McDonald’s Mobile Application - Louis Yong Yu Lee; Kai Sheng Yap; Wen Zhuo Yap; Mei Ting Yap; Ai Se Yeoh; Neha G; Abhishek M; Daisy Mui Hung Kee (Asia Pacific Journal of Management and Education (APJME), 2026)
This study examines how e-service quality influences customer e-satisfaction, e-loyalty, and brand equity in Malaysia, using the McDonald’s mobile application as the research context. Grounded in the Service Quality–Loyalty framework and Expectation-Confirmation Theory, the study distinguishes between e-service delivery quality, which reflects how effectively the application delivers services, and e-service outcome quality, which captures the value users obtain from using the app. Data were collected via an online survey of 157 Malaysian users with prior app usage experience. Using regression analysis in IBM SPSS, the findings indicate that both e-service delivery quality and e-service outcome quality play important roles in enhancing customer e-satisfaction and e-loyalty. However, loyalty is driven more strongly by the perceived quality of service outcomes than by satisfaction alone, suggesting that customers continue using the application primarily due to its reliability, convenience, and functional value. Customer e-loyalty also emerged as a key mechanism through which digital service experiences translate into stronger brand equity.